Acanmontanoside, a New Phenylethanoid Diglycoside from Acanthus montanus - Tripetch Kanchanapoom; Somsak Ruchirawat; Pawadee Noiarsa (Molecules, 2010)
A new phenylethanoid glycoside acylated with syringic acid, namely acanmontanoside, was isolated from the aerial portions of Acanthus montanus (Nees). T. Anderson, along with decaffeoylverbascoside, verbascoside, isoverbascoside, leucosceptoside A, (2R)-2-O-b-D-glucopyranosyl-2H-1,4-benzoxazin-3(4H)-one (HBOA-Glc), (2R)-2-O-b-D-glucopyranosyl-4-hydroxy-2H-1,4-benzoxazin-3(4H)-one (DIBOA-Glc), (3R)-1-octen-3-ol-3-O-b-D-xylopyranosyl-(1→6)-O-b-D-glucopyranoside and ebracteatoside B. The structure elucidations were based on physical data and spectroscopic analyses including 1D- and 2D-NMR.